2013
DOI: 10.4209/aaqr.2012.08.0224
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Passively-Measured Ozone, Nitrogen Dioxide and Sulfur Dioxide Concentrations in the Athabasca Oil Sands Region of Alberta, Canada

Abstract: The Athabasca Oil Sands Region (AOSR) in northeastern Alberta, Canada has attracted much international attention in recent years due to the increased level of oil sands operations. A passive sampling program was initiated in 1999 to monitor ozone (O 3 ), nitrogen dioxide (NO 2 ) and sulfur dioxide (SO 2 ) in the AOSR for the estimation of the exposure of the forest monitoring sites and the characterization of temporal trends. Since 1999, highest concentrations of O 3 and NO 2 occurred in April and winter, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
2
14
2
1
Order By: Relevance
“…This may have been due to the lower temperatures coupled with a greater frequency of high atmospheric stability and mixing height conditions during winter resulting in higher concentrations (Atkins and Lee, 1995). In rural Alberta the use of wood combustion and fossil fuel combustion for residential heating, and industrial emissions during winter can cause higher NO 2 and SO 2 concentrations compared to summer (Hsu, 2013;WBK, 2007). O 3 concentrations were particularly dominant in the spring and early summer (March through June) period, where maximum concentrations ranged from 35 to 56 ppb.…”
Section: Ambient Levels and Seasonal Variationmentioning
confidence: 96%
See 2 more Smart Citations
“…This may have been due to the lower temperatures coupled with a greater frequency of high atmospheric stability and mixing height conditions during winter resulting in higher concentrations (Atkins and Lee, 1995). In rural Alberta the use of wood combustion and fossil fuel combustion for residential heating, and industrial emissions during winter can cause higher NO 2 and SO 2 concentrations compared to summer (Hsu, 2013;WBK, 2007). O 3 concentrations were particularly dominant in the spring and early summer (March through June) period, where maximum concentrations ranged from 35 to 56 ppb.…”
Section: Ambient Levels and Seasonal Variationmentioning
confidence: 96%
“…Historical field studies of these passive samplers (EPCM, 2000;Brassard, 2001;WBK, 2007;RWDI, 2008;Hsu et al, 2010;Hsu, 2013) are limited either by small sample size or by being qualitative rather than quantitative. Therefore, a robust estimate of the field measurement errors (expressed by precision and accuracy) of the passive samplers was sought to aid in the interpretation of time-weighted average ambient concentrations of SO 2 , NO 2 , and O 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, continuous and passive measurement techniques have different purposes and uses, therefore it is suggested that the data from these two methods can be suitably compared for general trends rather than compared on an absolute basis (Hsu, 2013).…”
Section: Comparison Of Passive With Active (Continuous) Monitors At Cmentioning
confidence: 99%
“…Ambient concentrations o f these species were measured using passive diffusive samplers, which have been widely used across America and Europe for the assessment o f atmospheric NO2 and SO2 concentrations (e.g. Bytnerowicz et al, 2010;Campos et al, 2010;Cape et al, 2004;Cox, 2003;Hafkenscheid et al, 2009;Hagenbjork-Gustafsson et al, 1999;Hsu, 2013;Kirchner et al, 2005;Legge et al, 1996;Tang et al, 1997;Tang et al, 1999;Tang et al, 2001;Van Reeuwijk et al, 1998;Vardoulakis et al, 2009;Zbieranowski and Aheme, 2012a) and for filling gaps in monitoring networks (Zbieranowski and Aheme, 2012a). To the best of our knowledge, there are no published articles available that describe the ambient air concentrations o f Northeastern B.C.…”
Section: Introductionmentioning
confidence: 99%